Virtual screening of natural anti-filarial compounds against glutathione-S-transferase of Brugia malayi and Wuchereria bancrofti - Saeed, Mohd; Imran, Mohd; Baig, Mohd Hassan; Kausar, Mohd Adnan; Shahid, SMA; Ahmad, Irfan (Cellular and Molecular Biology, 2018)
Glutathione-S-transferase also referred as GST is one of the major detoxification enzymes in parasitic helminths. The crucial role played by GST in various chronic infections has been well reported. The dependence of nematodes on detoxification enzymes to maintain their survival within the host established the crucial role of GST in filariasis and other related diseases. Hence, this well-established role of GST in filariasis along with its greater nonhomology with its human counterpart makes it an important therapeutic drug target. Here in this study, we have tried to explore the inhibitory potential of some of the well-reported natural ant-filarial compounds against the GST from Wuchereria bancrofti (W.bancrofti) and Brugia malayi (B.malayi). In silico virtual screening, approach was used to screen the selected natural compounds against GST from W.bancrofti and B.malayi. On the basis of our results, here we are reporting some of the natural compounds which were found to be very effective against GSTs. Along with we have also revealed the characteristic of the active site of BmGST and WbGST and the role of important active site residues involve in the binding of natural compounds within the active site of GSTs. This information will oped doors for using natural compounds as anti-filarial therapy and will also be helpful for future drug discovery.